HUBUNGAN TINGKAT PENGETAHUAN TENTANG SADARI DENGAN PERILAKU SADARI SEBAGAI DETEKSI DINI KANKER PAYUDARA PADA MAHASISWA D-III KEBIDANAN KHARISMA HUSADA BINJAI TAHUN 2017 - Ronilda Tambunan (Akademi Keperawatan Kesdam I/Bukit Barisan Medan, 2017)
Breast cancer cases in developed countries has reached more than 580.000 cases each year and 64% of these cases died of this disease. An estimated 10 of the Indonesian population of 100.000 are suffered and 70% of the patients examined her on the advanced stage. Being lazy and embarrassed to show the breast are some factors that cause the patient less understanding about breast cancer. Student who was educated in the health sector in general has gained knowledge about BSE so that tends to establish a positive attitude that is reflected in their behavior. The purpose of this study was to determine the correlation between the knowledge level of BSE and BSE behavior. This research uses an analytic observational study design with cross sectional approach. The sampling technique used is simple random sampling with a number of research subjects consisted of 93 female college students of DIV Midwifery Studies Program of Medical Faculty of UNS in VI and VIII semester. Measuring instruments used are questionnaires and statistical analysis used was Spearman's Rank with the aid of a computer program SPSS version 17.00. The results of the 93 respondents indicated that there were 53 people (57%) had a high knowledge level of BSE, 38 people (40.8%) had an average knowledge level of BSE and two people (2.2%) had low knowledge level of BSE. While there were 44 people (47.3%) had a good BSE behavior, 41 people (44.1%) had a good enough BSE behavior and eight people (8.6%) had an unfavorable BSE behavior. The statistical result is π = 0.404 with a significance of 0.00 (P < 0.05).